Development and evaluation of an interactive karate e-module for elementary physical education - Juli Harmet; Syahrial Bakhtiar; Alnedral Alnedral; Aldo Naza Putra (Journal of Educational and Learning Studies, 2026)
Objective: This study aimed to develop a valid, practical, and effective Physical Education, Sports, and Health (PESH) E-Module on karate for Phase C elementary school students. Methods: A Research and Development approach employing the ADDIE model was adopted. The E-Module was validated by content, media, and language experts, while practicality was evaluated through teacher and student questionnaires. Its effectiveness was examined using a quasi-experimental nonequivalent control group design with pre-test and post-test assessments. Results: The E-Module achieved an overall validity score of 92.67%, teacher practicality ratings of 95.2–98.4%, student responses of 80–97%, and an N-Gain of 80% in the experimental group, outperforming the control group (43%). Conclusions: The developed E-Module is a valid, practical, and effective digital learning resource that enhances elementary students' karate learning outcomes and supports technology-enhanced Physical Education.